HAK MEMILIH TNI DAN POLRI DALAM PERSPEKTIF HUKUM POSITIF DAN HAK ASASI MANUSIA - Salsabila, Mikyal (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Members of the TNI and POLRI as part of Indonesian citizens should have human rights, especially the political right to vote in elections. However, in reality, the right to vote for these two agencies is limited by the provisions in force in the legislation. Therefore, this research was conducted to analyze the provisions on the right to vote for members of the TNI and POLRI from a positive law and human rights perspective. This research uses normative juridical methods such as a conceptual approach, a state approach, a historical approach and an analytical approach. Based on the research results, there is a decline in democracy looking at the history of elections in 3 periods, namely the old order, the new order and the reform era. Apart from that, there is a lack of synchronization between positive legal provisions and each other which regulate human rights and political rights of Indonesian citizens